Combined synthetic and |S| chart for monitoring process dispersion. Issue 7 (9th August 2017) - Lee, Ming Ha; Khoo, Michael B. C.
ABSTRACT: This article proposes a multivariate control chart, the syn-|S | chart, which comprises a standard |S | subchart and a multivariate synthetic sample generalized variance |S | (synthetic |S |) subchart, for detecting shifts in the covariance matrix of a multivariate normally distributed process. A procedure for the optimal design of the syn-|S | chart by minimizing the average extra quadratic loss is provided. The syn-|S | chart has better overall performance compared to the synthetic |S | chart and the standard |S | chart, based on the zero-state and steady-state modes. An example is given to illustrate the operation of the synthetic |S | chart.